Armochaetoglasins A–I: Cytochalasan alkaloids from fermentation broth of Chaetomium globosum TW1-1 by feeding L-tyrosine. (December 2018) - Gao, Weixi; Sun, Weiguang; Li, Fengli; Chai, Chenwei; He, Yan; Wang, Jianping; Xue, Yongbo; Chen, Chunmei; Zhu, Hucheng; Hu, Zhengxi; Zhang, Yonghui
Abstract: By feeding L -tyrosine into the culture medium, nine undescribed compounds, termed as armochaetoglasins A–I, together with three known analogues, namely armochaetoglobin E, chaetoglobosin V, and chaetoglobosin J, were isolated and identified from the medicinal terrestrial arthropod-derived fungus Chaetomium globosum TW1-1. Their structures were elucidated by means of NMR spectroscopy, single-crystal X-ray crystallography, and comparison of their electronic circular dichroism (ECD) spectra. Structurally, armochaetoglasin A represented the first tyrosine-derived cytochalasan alkaloid characterized by a 13-membered carbocyclic ring system; armochaetoglasins B and C possessed a rare 19, 20- seco -chaetoglobosin skeleton. Armochaetoglasin B, chaetoglobosin V, and chaetoglobosin J showed weak cytotoxic activity with IC50 values ranging from 19.5 to 34.72 μ M. Graphical abstract: Nine undescribed cytochalasan alkaloids and three known analogues were isolated from the medicinal terrestrial arthropod-derived fungus Chaetomium globosum TW1-1. Armochaetoglasin B, chaetoglobosin V, and chaetoglobosin J showed weak cytotoxic activity. Image 1 Highlights: Armochaetoglasins A–I were isolated from the fungus Chaetomium globosum TW1-1. Chemical structures were ascertained by spectroscopic and mass spectrometric analyses. Absolute configurations were assigned by crystallography and experimental ECD analyses. Armochaetoglasin B, chaetoglobosin V, and chaetoglobosin J showed cytotoxic activity.